2003
DOI: 10.1136/bjo.87.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 5% povidone-iodine solution against 1% povidone-iodine solution in preoperative cataract surgery antisepsis: a prospective randomised double blind study

Abstract: Background/aim: Povidone-iodine (PI, Betadine) is routinely used as a preoperative topical antiseptic in cataract surgery as it has been shown to reduce the incidence of postoperative endophthalmitis. However, the concentration used clinically is variable. In vitro studies have shown that PI is paradoxically more effective at lower concentration. This study was undertaken to determine if this effect was reproducible in vivo. Methods: A prospective randomised double blind study was carried out in the ophthalmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 19 publications
1
87
0
11
Order By: Relevance
“…A United Kingdom study of 100 patients, which compared the effects of 1% and 5% povidone-iodine solutions, demonstrated that irrigation with the 5% solution led to a 60% reduction in colony forming units, compared to a 16.7% reduction using the 1% solution. This result was significant (p<0.05), and the difference more evident when the initial bacterial load was higher (13) . In our study, irrigation of the conjunctival fornices with 5% povidone-iodine achieved a major reduction (60.8%) in conjunctival flora.…”
Section: Discussionmentioning
confidence: 48%
“…A United Kingdom study of 100 patients, which compared the effects of 1% and 5% povidone-iodine solutions, demonstrated that irrigation with the 5% solution led to a 60% reduction in colony forming units, compared to a 16.7% reduction using the 1% solution. This result was significant (p<0.05), and the difference more evident when the initial bacterial load was higher (13) . In our study, irrigation of the conjunctival fornices with 5% povidone-iodine achieved a major reduction (60.8%) in conjunctival flora.…”
Section: Discussionmentioning
confidence: 48%
“…Kiffney et al showed that reducing full strength 10% povidone iodine by half greatly reduced ocular irritation while maintaining bactericidal efficacy [15]. Diluting the strength of povidone iodine any further results in less bactericidal efficacy [6]. With the recent increase in the number of intravitreal injections performed for different retinal disorders, identifying the most effective application technique of povidone iodine is of significant importance.…”
Section: Discussionmentioning
confidence: 98%
“…Jumlah bakteri akan berpengaruh terhadap daya kerja povidone iodine, dimana jumlah iodine bebas yang dilepas sebagai bahan aktif bakterisidal akan berkurang efektifitasnya dengan jumlah bakteri awal yang tinggi. 6 Poviodone iodine memiliki sifat anti bakteri utamanya melalui mekanisme dimana povidone membawa senyawa iodine bebas masuk menembus membran sel. Senyawa iodine memiliki sifat yang sitotoksik sehingga mampu membunuh sel bakteri.…”
Section: Pembahasanunclassified